From sterile urine to dysbiotic ecosystem: The role of urobiome disruption in recurrent urinary tract infection - Antony Hamlin Joseph; Sunil Manjima; Franklin Frieno Frank (The Ukrainian Scientific Medical Youth Journal, 2026)
Introduction. Recurrent urinary tract infections are best conceptualized as a disorder of microbial disequilibrium in which disruption of the normally protective urogenital ecosystem permits repeated pathogen establishment and persistence. Rather than representing isolated infectious episodes, recurrence reflects a failure of microbial homeostasis across interconnected niches, including the urinary tract, vagina, and gastrointestinal system. A defining feature of this condition is the decline of protective commensal organisms, particularly Lactobacillus species, accompanied by increased dominance of opportunistic uropathogens such as Escherichia coli, Klebsiella pneumoniae, Enterococcus faecalis, and Proteus mirabilis, which collectively undermine colonization resistance and promote infection susceptibility. Aim. The aim of this review is to characterize recurrent urinary tract infections as a manifestation of persistent microbial imbalance and adaptive pathogen survival, with particular attention to the role of the urogenital and gastrointestinal microbiome, biofilm formation, intracellular bacterial reservoirs, and microbiome-oriented therapeutic approaches. Materials and Methods. This review summarizes current concepts regarding microbial disequilibrium, pathogen persistence mechanisms, antimicrobial-associated microbiome disruption, the gut–bladder axis, vaginal microbiota alterations, and emerging strategies aimed at restoring microbial equilibrium in recurrent urinary tract infections. Results. This imbalance is often reinforced by repeated courses of antimicrobial therapy, which, while targeting acute infection, inadvertently deplete beneficial microbial populations, reduce ecological diversity, and select for resistant strains with enhanced survival capacity. Central to recurrence is the ability of pathogens to evade eradication through specialized persistence strategies. These include the development of biofilms that function as structured, matrix-enclosed communities with reduced metabolic activity and limited antibiotic accessibility, as well as intracellular bacterial reservoirs that enable pathogens to remain concealed within urothelial cells in a dormant state. Persister cells further contribute by adopting transiently inactive phenotypes that tolerate antimicrobial exposure and later repopulate once treatment pressure is removed. In parallel, the gastrointestinal tract acts as a continual source of uropathogens, facilitating reinfection through repeated transfer along the gut–bladder axis, while alterations in vaginal microbial composition—particularly those associated with hormonal changes—further compromise local defense mechanisms. Collectively, these processes create a self-sustaining cycle of microbial instability and infection recurrence. Conclusions. Consequently, effective management requires a shift away from pathogen elimination alone toward strategies that restore and maintain microbial equilibrium. Interventions such as targeted probiotics, hormonal therapies, dietary modulation, and emerging microbiome-based approaches aim to reinforce beneficial microbial communities and enhance host resistance. Nonetheless, variability in clinical response highlights the need for improved mechanistic understanding and standardized therapeutic frameworks. In this context, recurrent urinary tract infection should be regarded as a manifestation of persistent ecological disruption and adaptive microbial survival, necessitating comprehensive approaches that address both microbial composition and functional resilience.